The Dynamic Impact of Foreign Debt-Based Education and Health Investment on Economic Growth in Asean-5 Countries - Ade Qusrinda; Sofyan Syahnur; Muhammad Nasir (Research Collaboration Community (RCC), 2025)
This study examines the use of external debt to finance health and education in order to promote economic growth in developing countries, focusing on five ASEAN member countries namely Cambodia, Indonesia, Laos, the Philippines and Thailand. The Johansen, Pedroni and Kao cointegration test results indicate the existence of a long-run relationship between the independent and dependent variables. The panel data Autoregressive Distributed Lag (ARDL) model is used to analyze the short-term and long-term effects using annual data for the period 2000-2022. The results of this study found that in the short run education financing has a positive effect while health, labor and capital financing have a negative impact on economic growth. The results in the long run found that education and health financing have a negative impact on economic growth in ASEAN-5 countries due to too high debt and inefficiency in allocation is also one of the reasons the long-term effect has not been realized. Labor and capital have a positive impact on economic growth this is due to high external debt in many ASEAN-5 countries is also high, although this is not proportional to external debt and the effect is very small. Based on the findings of this study, it is recommended that governments in ASEAN-5 countries continue to improve efficiency in managing and allocating foreign debt towards education and health. In addition, serious efforts are needed for more assertive and targeted policies related to the use of foreign debt.